2017 IEEE 4th International Conference Actual Problems of Unmanned Aerial Vehicles Developments (APUAVD) 2017
DOI: 10.1109/apuavd.2017.8308820
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned aerial vehicle navifation system based on IEEE 802.15.4 standard radiounits

Abstract: Modern unmanned aerial vehicle navigation systems are highly dependent on Global Positioning System signals. Since Global Positioning System signals in dense urban housing areas, in tunnels or indoors may be unreliable, unmanned aerial vehicle will not be able to fulfill its tasks if needed to pass such zones. An unmanned aerial vehicle navigation system based on on the increasingly popular radio standard IEEE 802.15.4 / ZigBee is proposed. A description of such networks and their advantages for unmanned aeria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The ZigBee protocol is used by Mushtaq et al [28], Min and Nam [29] to perform fly-by-sensors (FBS) flight control with stable flight formation, while Sineglazov and Daskal [30] propose a UAV navigation system for dense urban areas in tunnels or indoor environments. The flight planning and formation model is discussed in Lee et al [31], Park et al [32] where an effective routing protocol for navigation control and an information sharing system with onboard sensors and flight path formation algorithms are proposed for various UAVs.…”
Section: Introductionmentioning
confidence: 99%
“…The ZigBee protocol is used by Mushtaq et al [28], Min and Nam [29] to perform fly-by-sensors (FBS) flight control with stable flight formation, while Sineglazov and Daskal [30] propose a UAV navigation system for dense urban areas in tunnels or indoor environments. The flight planning and formation model is discussed in Lee et al [31], Park et al [32] where an effective routing protocol for navigation control and an information sharing system with onboard sensors and flight path formation algorithms are proposed for various UAVs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sineglazov and Daskal [18] propose an UAV navigation system using radio units based on IEEE 802.15.4. They showed that it is possible to use a wireless network to estimate the location of a UAV.…”
Section: Related Workmentioning
confidence: 99%